TEACHING WRITING DESCRIPTIVE TEXT IN BLENDED LEARNING - Yeni Erlita (Universitas Negeri Medan, 2022)
Abstract This study related with blended learning used by the teachers in teaching writing descriptive text. This study was qualitatively conducted that involved English teachers. The data were collected by using recording, interview and observing the whole processes of teaching writing. The findings of this study showed that teachers used the three processes in blended learning setting, such as: conventional learning, emphasizes learning actively and interactive learning. It was also found that the use of blended learning was used in the scientific approach activity. And the steps in the scientific approaches applied in learning process in three activities, beginning activity, core activity, and closing activity. There were four problems faced by teachers in using blended learning by two platforms such as the problem of the traditional mind - set, the problem of managing, assessing learner progress, bandwidth, and confusion in using the application. Teachers faced different problems in the learning process.Keywords: Blended learning, teaching, writing, descriptive text, learning process.